Synthesis, Characterization of Trinuclear Containing Se (II) Donar Group of Ni (II) Complexes (International Journal of Scientific Research in Science and Technology, 2025)
For many years, metal complexes have piqued attention. Selenium atoms play key role in coordination of metal at the active sites of numerious metal biomolecules. The development of the field of bioinorganic chemistry has increased the interest in complexes of Selenium and serve as multifunctional properties. In view of contribution of studies on Selenium complexes containing ligands, we have prepared trinuclear complexes of Selenium (II) having formula [Se2NiMcBr2]. Selenium is an essential component of several measure metabolic pathways, including thyroid hormone metabolism antioxidant defence system and immune function. The decline in blood selenium concentration in the several part of the world as per WHO report has therefore several potential public health, particularly in related to the chronic disease. Selenium is the only one for which incorporation into protein is generaly encoded, as the constitutive part of the twenty one amino acid, selenocysteine. Anticancer properties of Selenium and its complexes are most important in medicinal chemistry. Being relevant to redox processes in living organism selenide in corporeted withing a drug structure have been most effective. Selenium available in biological system. It leads to multifunctional properties as fungicides, anticancerous agents, arrestors of human immuno deficiency virus infections.
Keywords: Selenium; antioxidant; Organoseleniumazone; bis-naphathaldehyde selenide; [dibromo-bis-(dihydrazone nickel (II)]; anticancer agent